ANALISIS SEMIOTIKA ROLAND BARTHES DALAM IKLAN RAMAYANA EDISI RAMADHAN 2018 #KERENLAHIRBATIN - Wulandari, Sri; Arifianto, Pungky Febi (Institut Seni Indoensia Surakarta, 2022)
Ramadan moments provide business opportunities in various fields in various sectors. One of them is in the fashion sector because Ramadan is closely related to Eid. Eid itself is often associated with new clothes. Ramayana Lestari Sentosa is one of the major department stores in Indonesia. Ramayana Department Store often steals attention through its iconic advertisements. One of the iconic Ramayana advertisements is the Ramadhan (2018) edition #KerenLahirBatin edition. This study examines the meaning of the Ramayana advertisement in the Ramadhan (2018). The method used in this research is content analysis method using Rolland Barthes' semiotic approach. The results of the analysis show two things, namely that there is an ideology of capitalism that operates in the Ramayana advertisement of the Ramadhan (2018) and the existence of a perpetuation of patriarchal discourse which views that men are superior while women are inferior, especially in the lower middle social class.